the used code mixing and code switching by students in classroom interaction - Septi Kania Dewi; Rahma Ilyas; Afif Fakhruddin (National Conference on Language, Education, and Technology Proceeding, 2022)
Despite several researches have been conducted to investigate the issue of code-switching and code mixing, the findings of this research are significant as they can assist both students and teachers to consider the use of code-switching and code mixing in classroom interaction, specifically in Indonesia. The aim of this research 1) to classify the type of code mixing and code switching that used by student in classroom interaction, 2) to interpret the function of code mixing and code switching that used by student in classroom interaction. This research employed descriptive qualitative method. Data collection instruments were the observation and interview. The data of type of code mixing were analyzed based on Hoffman’s theory, namely intra-sentential code mixing, intralexical code mixing and involving a change of pronunciation. The data of type of code switching were analyzed based on Poplack’s theory, namely inter-sentential switching, intra-sentential switching and tag switching. The most common used is inter-sentential switching and intra sential switching. The functions of code mixing and code switching were analyzed by Marsigan’s theory, namely, quotation, addressee specification, repetition, interjection, message qualification, personalization and objectivization, and facility of expression. The most usually function is facility of expression.